The perspectives of nursing students regarding the incorporation of African traditional indigenous knowledge in the curriculum - Roinah N. Ngunyulu; Nombulelo Sepeng; Mabitja Moeta; Sanele Gambu; Fhumulani M. Mulaudzi; Mmampeko D. Peu (AOSIS, 2020)
Background: South Africa was caught off guard by the student unrest in 2015 and 2016. This unrest was named the #fees must fall campaign. During this campaign, students raised the issue of decolonisation of the curriculum, challenging the higher education fraternity and the academic community. This was based on the fact that the existing curriculum has inadequate content on African traditional indigenous knowledge (ATIK), and continues to use the Western approach to address the needs of a multicultural, multiracial and multi-ethnic societies. Institutions responded by initiating dialogues regarding decolonisation of the curriculum in senates, scholars and between different health professional bodies. Aim: This article aimed to explore and describe the perspectives of nursing students regarding incorporating ATIK into the curriculum. Methods: Using a participatory transformative approach, researchers and participants worked collaboratively to inform social change. Participants comprised nursing students. The academics, traditional health practitioners, indigenous knowledge holders and primary health care nurses formed the panellists. Data were collected through one communal dialogue workshop, which lasted for 8 hours, tea and lunch included. Data were analysed thematically. Results: Students' perspectives emerged strongly as four themes, namely, politics of identity, displacement and distortion, curriculum content and institutional resistance. Students expressed that the current education system results in an identity crisis. The existing curriculum does not adequately convey an understanding of ATIK; it is displaced and distorted. Conclusion: Nursing science has great potential to incorporate the wealth of ATIK into its curriculum. In spite of a vibrant and rich cultural heritage, the ATIK specific to nursing sciences still needs to be incorporated into the existing curriculum in a responsive and relevant manner.